Transcription Factor Repertoire of Necrotrophic Fungal Phytopathogen Ascochyta rabiei: Predominance of MYB Transcription Factors As Potential Regulators of Secretome - Verma, Sandhya; Gazara, Rajesh K.; Verma, Praveen K. (Frontiers in Plant Science, 2017)
Transcription factors are the key players in gene expression and their study is highly significant for shedding light on the molecular mechanisms and evolutionary history of organisms. During host-pathogen interaction, extensive reprogramming of gene expression facilitated by transcription factors is likely to occur both in host and pathogen. To date, the knowledge about transcription factor repertoire in filamentous fungi is in infancy. The necrotrophic fungus Ascochyta rabiei, that causes destructive Ascochyta blight (AB) disease of chickpea (Cicer arietinum), demands more comprehensive study for better understanding of Ascochyta-legume pathosystem. In the present study, we performed the genome-wide identification and analysis of transcription factors in A. rabiei. Taking advantage of A. rabiei genome sequence, we used a bioinformatic approach to predict the transcription factor repertoire of A. rabiei. For identification and classification of A. rabiei transcription factors, we designed a comprehensive pipeline using a combination of BLAST and InterProScan software. A total of 381 A. rabiei transcription factors were predicted and divided into 32 fungal specific families of transcription factors. The gene structure, domain organization and phylogenetic analysis of abundant families of A. rabiei transcription factors were also carried out. Comparative study of A. rabiei transcription factors with that of other necrotrophic, biotrophic, hemibiotrophic, symbiotic and saprotrophic fungi was performed. It suggested presence of both conserved as well as unique features among them. Moreover, cis-acting elements on promoter sequences of earlier predicted A. rabiei secretome were also identified. With the help of published A. rabiei transcriptome data, the differential expression of transcription factor and secretory protein coding genes was analyzed. Furthermore, comprehensive expression analysis of few selected A. rabiei transcription factors using quantitative real-time polymerase chain reaction (qRT-PCR) revealed variety of expression patterns during host colonization. These genes were expressed in at least one of the time points tested post infection. Overall, this study illustrates the first genome-wide identification and analysis of transcription factor repertoire of A. rabiei. This work would provide the basis for further studies to dissect role of transcription factors in the molecular mechanisms during A. rabiei-chickpea interactions.